A theory of standing meanders of the Antarctic Circumpolar Current and their response to wind - Xihan Zhang; Maxim Nikurashin; Beatriz Pena-Molino; SR Rintoul; Edward Doddridge (2023)
Standing meanders of the Antarctic Circumpolar Current (ACC) and associated eddy hotspots play an important role for the meridional heat flux and downward momentum transfer in the Southern Ocean. Previous modelling studies show that the vorticity balance characterising standing meanders in the upper ocean is dominated by advection of relative vorticity and stretching. Through the adjustment of this vorticity balance, standing meanders have been suggested to provide a pathway for the transfer of the momentum input by the wind from the surface to the bottom, leading to stronger bottom flows and energy dissipation. However, the dynamics governing the meander formation and its adjustment to wind remain unclear. Here we develop a quasi-geostrophic theory and combine it with a regional model of the Macquarie Ridge region and an idealized channel model to explore the dynamics and vertical structure of standing meanders of the ACC. The results show that the entire vertical structure of the meander, including its dynamics in the upper ocean, is controlled by the bottom flow interacting with topography. Based on our results, we suggest a novel mechanism for the response of the ACC to wind in which ‘flexing’ of the meander, or change in its curvature, is a response to changes in the bottom (barotropic) flow. Stronger bottom flow in response to stronger wind interacts with topography and generates a larger amplitude Rossby wave propagating into the upper ocean. The ACC mean shear aloft amplifies the Rossby wave and leads to a larger amplitude meander in the upper ocean dominated by advection of relative vorticity and stretching.